Comparison of Adverse Maternal Outcome in Early Onset Versus Delayed Onset Preeclampsia - Saba Jehangir, Rohana Salam, Nasreen Akhtar, Nimra Bashir, Sara Akram, Farzana Sabir, Shazia Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the association of adverse maternal outcome with early onset preeclampsia than delayed onset preeclampsia. Study Design: Cohort study. Place and Duration of Study: Department of Obstetrics & Gynecology Unit-II, DHQ Hospital, Mirpur, AJK from 30th December 2020 to 29th June 2021. Methodology: A total of 60 (30 early onset pre-eclampsia and 30 delayed onset pre-eclampsia) females of age 18-40 years with parity <5, presenting at gestational age >24 weeks were included. Patients with chronic or gestational diabetes (BSR>186mg/dl), chronic hypertension (BP≥140/90mmHg), cardiac disease (on medical record), multiple gestation (on ultrasound), abnormal placenta (abruption, previa, accrete, increta, percreta on ultrasound) were excluded. Females were evaluated for eclampsia (BP>160/100mmHg along with convulsions), DIC, HELLP syndrome and avascular tubular necrosis by using blood samples and ultrasound findings. Results: The adverse maternal outcome i.e. eclampsia was recorded in 11 (36.67%) in exposed group (early onset pre-eclampsia) versus 04 (13.33%) in unexposed group (delayed onset pre-eclampsia) (p= 0.053; relative risk = 2.75), acute tubular necrosis was recorded in 05 (16.67%) in exposed group (early onset pre-eclampsia) while 00 (0.0%) in unexposed group (delayed onset pre-eclampsia) (p = 0.099; relative risk = 11.00), DIC was recorded in 03 (10.0%) versus 00 (0.0%) respectively (p= 0.192; relative risk = 7.00) and HELLP syndrome in 06 (20.0%) versus 00 (0.0%) respectively (p = 0.076; relative risk = 13.0). Practical Implication: We recommend that a proper protocol should be designed in these high risk patients for antenatal monitoring and proper management plans in order to reduce the morbidity and mortality of the mother and fetus. Conclusion: This study concluded that adverse maternal outcome is higher in early onset preeclampsia as compared to delayed onset preeclampsia. Keywords: Preeclampsia, Adverse Maternal Outcome, Eclampsia.